Images and Problems of Modern Realism — in the Context of the Exhibitions of Young Artists of the Union of Artists of St. Petersburg in 2015–2017 - Fomina, Maria S. (Actual Problems of Theory and History of Art, 2018)
The text analyses recent exhibitions of the young painters and graphics of the Union of Artists of St. Petersburg. The works of different genres demonstrate the traditions of Russian academic school and high professional level of young masters. Their predecessors were famous academicians: Andrey Mylnikov, Evsey Moiseenko, Boris Ugarov, and others. At the same time, the paitings of the young graduates of the Academy of Fine Arts are dedicated to the complicated and tragic themes of history, war and peace, show the tendency to the lyrical and philosophic interpretation of these subjects. The artists appeal to symbolic forms, the Bible, and mythological associations. They use the iconography of lamentation, pieta, and deisis, preferring bas-relief and frieze types of composition. Pray, reminiscence, vision, contemplation — these are the forms of interpretation of historic themes in paintings by Alexei Kalinin and Andrei Filippov, Sergei Sekirin and Vadim Kaghdaev. In the genre of still life, Konstantin Grachev creates the symbolic images of the war times using hyper-realistically painted trench coat, blouse, black bread. Generally, the staged still life is one of the most popular genres in the painting of the young masters. “Polyrealistic” artistic conscience uses all styles and movements in figurative art: Neo-academism, Impressionism, Hyperrealism, Symbolism, and others. However, the real idol of the young masters of realistic art based on academic school is pure beauty, which triumphs over the tragedy of human life,on academic school is pure beauty, which triumphs over the tragedy of human life,horrors of war, and death.
Keywords: realistic art; portrait; landscape; still life; academic school